Ordinance no. A-17, § 2, Wilbur, Washington Town Council, 1894 (preventing the concealed carry or discharge of firearms). - (:unkn) unknown (My University, 1894)
If any person shall within the corporate limits of the Town of Wilbur, fire or discharge any gun, rifle, fowling piece, pistol or any other firearm, they shall be deemed guilty of a misdemeanor, and upon conviction thereof shall be fined in any sum not exceeding twenty five dollars ($25.00) together with the cost of prosecution.
Keywords: DISCHARGE